2022
DOI: 10.1002/mar.21729
|View full text |Cite
|
Sign up to set email alerts
|

The influence of language style (formal vs. colloquial) on the effectiveness of charitable appeals

Abstract: This paper investigates the influence of language style (formal vs. colloquial) on the effectiveness of charitable appeals. Although prior research has found persuasive effects associated with colloquial language style, we propose that the influence of language style is context dependent. Charitable appeals generally address relatively serious topics. Since formal language style is more context congruent in communicating this seriousness, it should be more effective in expressing the emotional arousal or the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…As mentioned above, Pfeiffer et al (2023) investigated the impact of formal and informal language styles on the effectiveness of charitable appeals. They found experimental evidence that charitable appeals are more effective when a formal rather than informal language style is used.…”
Section: Linguistic Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned above, Pfeiffer et al (2023) investigated the impact of formal and informal language styles on the effectiveness of charitable appeals. They found experimental evidence that charitable appeals are more effective when a formal rather than informal language style is used.…”
Section: Linguistic Strategiesmentioning
confidence: 99%
“…The results of this experiment showed that participants were more likely to indicate support for the charity when presented with an appeal in a formal rather than a colloquial style. Pfeiffer et al (2023) argue that formal language is more congruent in communicating serious topics, and therefore increases charitable support. Importantly, although Pfeiffer et al (2023) found greater charitable support when formal language was used, the use of pronouns was not manipulated in their study.…”
Section: Linguistic Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies mainly include three categories of factors that affect the success of online donation projects. One such category includes platform and project factors, such as appeal style (Bruyn & Prokopec, 2013;Kamatham et al, 2021;Moon & Vanepps, 2022), aid effectiveness and framing (Metzger & Günther, 2019), goal gradient (Kivetz et al, 2006), donation collection methods (Suk & Mudita, 2022), and the phrasing of projects (Gu & Chen, 2021;Lu et al, 2022;Pfeiffer et al, 2022).…”
Section: Online Donationmentioning
confidence: 99%
“…Existing studies mainly include three categories of factors that affect the success of online donation projects. One such category includes platform and project factors, such as appeal style (Bruyn & Prokopec, 2013; Kamatham et al, 2021; Moon & Vanepps, 2022), aid effectiveness and framing (Metzger & Günther, 2019), goal gradient (Kivetz et al, 2006), donation collection methods (Suk & Mudita, 2022), and the phrasing of projects (Gu & Chen, 2021; Lu et al, 2022; Pfeiffer et al, 2022). The second category includes initiator factors, such as demographic characteristics (X. Hou et al, 2022), social networks (Castillo et al, 2014; Jiao et al, 2021; Liu et al, 2022), stakeholder support and individual prestige (X. Hou et al, 2022).…”
Section: Theory and Hypothesismentioning
confidence: 99%